Music festivals and regional development policy: towards a festival ecology - Gibson, Chris (Perfect Beat, 2014)
This article examines the policy significance of festivals in regional development. It draws on experience conducting research on, and working with, festivals in rural and regional Australia for over a decade. Gibson summarizes the role of festivals in a broad spectrum of regional development concerns, from direct economic impacts to benefits for community, musical work and well-being. A perspective is offered that seeks to integrate questions of cultural identity, belonging, economy and place—and the music itself. He argues that from a regional development policy perspective the qualities of music festivals matter enormously: their format, management structure, values, ethics and decision-making, and degree of integration into local and regional community and economic life. Seemingly lucrative commercial festivals might well draw in large direct profits, but they do not necessarily contribute most effectively to regional development. Likewise, although small community and non-profit music festivals seem to offer limited job creation and visitor expenditure, when seen as part of a cumulative community festival ecology, they are an underestimated and yet important catalyst for cultural and regional economic development.